Pengaruh Teknik Cooperative Learning Berbasis Metode Think Pair Share Untuk Meningkatkan Pemahaman Materi Dasar-Dasar Elektronika - Habib Satria (PTE FTK UIN Ar-Raniry, 2021)
The accelerated development of the technological world cannot be separated from the materials of electronic components. Vocational schools are the most dominant schools in discussing electronics, but there are still many students who have abilities below the graduation standards that have been set in the subject of electronics basics. One of the causes of low learning outcomes is due to the lack of involvement of students in the learning process. Therefore it is necessary to think pair share method to spur student activeness and creativity during learning. The technique in doing this method is by students thinking, discussing and sharing material concepts directly with their classmates controlled by the teacher in material supervision. In addition, by using this method students are able to solve problems during the learning process well. This type of research is a Quasi Experiment with Posttest Only Control Design. The subjects of this study were students of class X SMK Negeri 1 Pariaman which consisted of two classes, namely X TITL-1 and X TITL-2. From these two classes were selected randomly where class X TITIL-1 was the experimental class and class X TITL-2 was the control class. To see students' initial abilities, an analysis of the posttest was carried out in the subject of Understanding the Basics of Electronics. Collecting data in this study using a learning outcome test (posttest) in the form of objective questions of 25 items. The data were analyzed using the two-mean difference test (t-test). Based on the results of the study, the posttest mean percentage of the experimental class was 77.14% and the control class was 55.14%. The results of this study indicate that there is a significant increase in student learning outcomes with a comparison of the think pair share method which is better than the conventional method.